Agricultural Extension in Kenya: lessons from India's Agricultural Extension Service - Nkurumwa 0, Agnes; Shelmith, Mucoki W (Journal of Agricultural Extension Management, 2019)
Agricultural Extension plays an important role in agriculture, by providing information and skills to farmers and also linking them to other players in the agriculture sector. Kenya, like many developing countries, has a publicly funded national extension service. Currently, the extension service in Kenya is undergoing major reforms on two fronts. The first, is the shift in approach, from the National Agriculture and Livestock Extension Programme (NALEP) to the Agriculture Sector Development Support Programme (ASDSP). The second is the devolution of agriculture to the counties, following the decentralization of government. These two situations have put Kenya's extension service at crossroads. The purpose of this paper is to highlight key success factors of India's extension service, with a view to highlighting best practices that Kenya can learn from India. India's agricultural extension service over the years has undergone a number of reforms, which have been effectively managed, resulting in tremendous success stories. Agriculture is devolved to the states, whereby each state is responsible for planning and implementing its own programmes, with general policy direction from the Federal Government. A key feature in planning is the participatory development of Strategic Research and Extension Plans, which ensure convergence of research and extension activities. Support to private extension service providers, and the extensive use of both traditional and modern ICTs also ensure significant coverage of farmers. Another feature is the provision of market-led extension services and weather-based advisory services. Universities and research organizations also play a key role in extension, with a key aspect being the Farm Science Centres (KVKs). There is a lot that Kenya can learn from India's extension service to ensure that current reforms are effectively managed, in order to have a vibrant agricultural extension service that will contribute to improved farmer livelihoods, food security and national economic growth.